A Comparative Study on the Impact of Technology-Enhanced Language Learning on ESL and EFL Students: A Systematic Review - UKE, Waode Ade Sarasmita; NONI, Nurdin; BASRI, Muhammad (Politeknik Negeri Ujung Pandang, 2024)
The goal of the study was to get a deeper understanding of how technology-enhanced language learning is utilized to teach and learn languages in higher education. This review follows the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) recommendations. The review begins with a description of the identification process. The best articles published between 2000 and 2022 have been selected to demonstrate how to compare significant aspects and valuable strategies. These articles were selected in accordance with EFL and ESL students. The results are organized into three categories, with the following topics occurring most frequently in the reviewed publications. Researchers may apply task-based learning, communicative, flipped classroom, and other instructional strategies. The second section deals with research instruments. The questionnaire, interview, test, forum group discussion, and observation were utilized to collect data. In conclusion, researchers have compiled a list of publications to be analyzed based on their most current research queries.